IbM-Kelompok Yasinan Dusun Tangar: Deteksi Dini Faktor Risiko Penyakit Kardiovaskular - Cholik Harun Rosjidi; Rika Mayasari; Dianita Rifqia Putri (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
The Community empowerment Program aims to improve the early awareness of cardiovascular disease (heart and strok) attacks on yasinan religious groups in Tangar, Jenangan sub-district, Ponorogo regency. Design to achieve these objectives with yasinan group empowerment program with two activities (1) provide health education to all group members and (2) Training of examination skills Blood Pressure, Blood Sugar, Cholesterol and First Aid in Emergency Heart and strok.. Target group program yasinan Tangar Jenangan, Ponorogo. Health education activities were held twice yasinan group meetings and training activities held 1 day. The yasinan group sends 10 people as representatives. The success of community service programs is assessed on the basis of increased knowledge values, passing the first emergency relief skills test and the realization of commitment in the form of a commitment statement. The first program form of training was held on July 31, 2017 with the following results: The training was attended by 10 members of the yasinan group. Training to improve knowledge and skills of early detection of risk factors for heart disease and strok (P = 0.000) Of the 10 participants 8 of them successfully passed the first aid skill test in an accident. Week 3 realizes the group's commitment to early detection of cardiovascular disease risk factors independently. These results illustrate the approach of effective religious groups to increase aware of cardiovascular disease attacks.